a,(x-3) ³-2(x-1)=x(x-2) ²-5x ² b,x(x+3) ²-3x=(x+2) ³+1

Question

a,(x-3) ³-2(x-1)=x(x-2) ²-5x ²
b,x(x+3) ²-3x=(x+2) ³+1

in progress 0
Sarah 3 ngày 2021-12-07T02:01:30+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-12-07T02:02:30+00:00

    Đáp án:

     $a,x=\frac{25}{21}\\
    b, x=\frac{-3}{2}$

    Giải thích các bước giải:

     $a,(x-3)^3-2(x-1)=x(x-2)^2-5x^2\\
    \Leftrightarrow x^3-3.x^2.3+3.x.3^2-3^3-2x+2=x(x^2-4x+4)-5x^2\\
    \Leftrightarrow x^3-9x^2+27x-27-2x+2=x^3-4x^2+4x-5x^2\\
    \Leftrightarrow x^3-9x^2+27x-27-2x+2-x^3+4x^2-4x+5x^2=0\\
    \Leftrightarrow 21x-25=0\\
    \Leftrightarrow 21x=25\\
    \Leftrightarrow x=\frac{25}{21}\\
    b,x(x+3)^2-3x=(x+2)^3+1\\
    \Leftrightarrow x(x^2+6x+9)-3x=x^3+3.x^2.2+3.x.2^2+2^3+1\\
    \Leftrightarrow x^3+6x^2+9x-3x=x^3+6x^2+12x+8+1\\
    \Leftrightarrow x^3+6x^2+9x-3x-x^3-6x^2-12x-8-1=0\\
    \Leftrightarrow -6x-9=0\\
    \Leftrightarrow -6x=9\\
    \Leftrightarrow x=\frac{-3}{2}$

    0
    2021-12-07T02:02:30+00:00

    Đáp án:

    $a,(x-3) ³-2(x-1)=x(x-2) ²-5x ²$

    $=> x³-9x²+27x-27-2x+2=x(x²-4x+4)-5x²$

    $=> x³-9x²+27x-27-2x+2=x³-4x²+4x-5x²$

    $=> x³-x³-9x²+4x²+5x²+27x-2x-4x-27+2=0$

    $=> 21x-25=0$

    $=> 21x=25$

    $=> x=25/21$

    Vậy $S=${$25/21$}

    $b,x(x+3) ²-3x=(x+2) ³+1$

    $=> x(x²+6x+9)-3x=x³+6x²+12x+8+1$

    $=> x³+6x²+9x-3x-x³-6x²-12x-1-8=0$

    $=> -6x-9=0$

    $=> -6x=9$

    $=> x=-1,5$

    Vậy $S=${$-1,5$}

    BẠN THAM KHẢO NHA!!!

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )